Peran Orang tua dan Fasilitas Modal dalam Menumbuhkan Motivasi Berwirausaha - Widya Nuriyanti (Peneliti.net, 2020)
Parents are a good example for their children. The desire of children that can be developed by their parents, will produce an idea, and the gifted talent, entrepreneurial values ​​that have been instilled early on at home, will leave a long lasting effect on the child, so it needs good efforts from parents. This study aims to determine the role of parents, and capital facilities, on entrepreneurship motivation in vocational students in Bogor. This research was conducted by a questionnaire method with a qualitative approach. The research sample was parents of vocational high school students in Bogor. The type of data is primary data with interview techniques and questionnaire data. The results showed that: The role of parents and capital facilities in fostering entrepreneurial motivation is the following, first, parents by providing capital although not much but can facilitate as initial capital, second, give examples, even if only indirectly, provide an understanding of independence does not depend on others, the three parties of the school help students can be entrepreneurs by facilitating products from students can be sold in school cooperatives.